PROFESIONALISME GURU SEJARAH DALAM IMPLEMENTASI KURIKULUM 2013 - Wardani, Hany Tyas; Agung, Leo; Yunianto, Tri (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
The purpose of this study were: 1) to determine the understanding of subject matter of teaching history related to the curriculum in 2013, 2) to determine whether history teachers to develop learning material of teaching creatively, 3) to determine how to asses historical teaching on SMA Negeri 6 Surakarta, 4 ) to determine the barriers faced history teacher at SMA Negeri 6 Surakarta, 5) to assess the efforts made history teachers in addressing the issue faced.The subjects were history teacher, vice principal part of the curriculum, and the school principal SMA Negeri 6 Surakarta. Data collection technique used interview, observation and document analysis. To be valid research data obtained, then researchers used data triangulation and triangulation methods. The analysis technique used by researchers is an interactive model. The procedure of the research is pre-court stage, the stage of field research, data analysis stage, and prepare the report stage. The results showed that: 1) the History Teacher at SMAN 6 Surakarta in making the RPP has met the standard curriculum, 2013. 2) The history teacher at SMA Negeri 6 Surakarta draw up an annual program, the semester program, and RPP. 3) The history teacher SMA Negeri 6 Surakarta attach four components namely.4) Constraints faced is not match between the material and available time, students are not familiar with active learning, lack of learning resources, and administration are too complicated. 5) Solutions are among others set up a video or picture, freeing students to develop material, the provision of WiFi for internet access. The school provides a blank empty form in the soft file in Excel format, making it easier for teachers and homeroom.